The Effect of Puzzle-Based Learning Media on Students' Learning Motivation in Indonesian Language among Fourth-Grade Students at SD Negeri 138 Pekanbaru - Resty Dwira; Febrina Dafit (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to determine the effect of using puzzle media on students' learning motivation in the Indonesian language subject in fourth grade at SD Negeri 138 Pekanbaru. The study used a quantitative approach with a pre-experimental method through a One Group Pretest–Posttest design. The study sample consisted of 37 fourth grade C students selected using a purposive sampling technique. The research instrument was a learning motivation questionnaire that had undergone validity and reliability tests. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and the paired sample t-test using the SPPS 25 program. The results showed that the average student learning motivation increased from 47.46% in the pretest to 67.08% in the posttest after the puzzle media was implemented. The results of the normality test showed that the data were normally distributed with a pretest significance of 0.549 and a posttest significance of 0.251. The paired sample t-test results obtained a significance value (Sig. 2-tailed) of 0.000 < 0.05, thus rejecting H₀ and accepting Hₐ. This suggests that puzzle media has a positive effect on student learning motivation in Indonesian. Thus, puzzle media significantly increases student motivation in Indonesian. This finding can be used as an alternative learning medium that can create a more active, engaging, and enjoyable learning environment, thereby increasing the learning motivation of elementary school students.